First clinical trial of tomographic neurofeedback in attention-deficit/hyperactivity disorder: evaluation of voluntary cortical control - Liechti, Martina Daniela; Brandeis, Daniel (Clinical neurophysiology, 2012)
Objective: Tomographic neurofeedback (tNF) training was evaluated as a treatment for attention-deficit/hyperactivity disorder (ADHD). To investigate the specificity of the treatment, outcomes were related to learning during tNF. Methods: Thirteen children with ADHD trained over 36 lessons to regulate their brain activity in the anterior cingulate cortex (ACC) using both theta-beta frequency and slow cortical potential (SCP) protocols. Thirty-channel electroencephalogram (EEG) was used to calculate low-resolution electromagnetic tNF and to assess the course of the training. Pre- and post-assessments included questionnaires, tests of attention, EEG recordings, and cognitive event-related potentials. Results: Despite behavioural improvement and EEG artefact reduction, only partial learning was found for ACC parameters. Successful regulation was observed only for a simple feedback variant of SCP training, but with ACC-specific effects. Over training, resting EEG analysis indicated individual frequency normalisation rather than unidirectional changes across subjects. Conclusions: These results indicate that clinical improvement after ACC-tNF training can parallel artefact reduction without substantial learning of improved cortical control. However, individual normalisation of resting EEG activity and partial SCP control proved possible in this specific brain region affected in ADHD using tNF. Further studies are needed to clarify which critical aspects mediate region-specific learning in neurofeedback. Significance: This study is the first to systematically investigate tNF in children suffering from a psychiatric disorder.
Gesehen am 28.08.2018